Analisis Makna Tekstual dan Kontekstual Hadist Tentang Niat Dalam Kitab Arba’in Nawawi - Alfinnaturrohmah; Dea Annisa; Nurul Hidayah (Al-Lahjah, 2023)
His study aims to make it easy for readers or listeners to understand a hadith as a whole and thoroughly. From a textual point of view, which focuses on the text or its pronunciation and from a contextual perspective, in order for the reader to know the context of the hadith, it can be from the context of the language or internal discourse and the context outside the language, which is also called the context of the situation outside. The method used in this research is descriptive qualitative and is library research. The data needed in this research comes from books, salaf books, documents, and several other publications related to the object of research. Because this research is aimed at studying a hadith matan, the data source is the book of hadith itself, namely the book of arba'in nawawi written by Abu Zakaria muhyiddin an-Nawawi and the search of his book and several books of his translations. The data in this study consist of an analysis of the hadith matan in the form of words, phrases, and sentences related to the textual and contextual meaning of the hadith matan in the chapter on intentions. Data collection techniques by reading, observing and analyzing through a semantic approach. Abstrak Penelitian ini bertujuan agar pembaca atau pendengar mudah dalam memahami sebuah hadits secara utuh dan menyeluruh. Dari segi tekstual yang berfokus pada teks atau lafadznya dan dari segi kontekstual yang mana agar pembaca mengetahui konteks dari hadits tersebut bisa dari konteks bahasa atau internal wacana dan konteks luar bahasa yang disebut juga dengan konteks situasi di luar. Metode yang digunakan dalam penelitian ini adalah deskriptif kualitatif dan merupakan penelitan kepustakaan (library research). Data yang diperlukan dalam penelitian ini bersumber dari buku-buku, kitab-kitab salaf, dokumen, dan beberapa terbitan lain yang berkaitan dengan objek penelitian. Karena penelitian ini ditujukan untuk mengkaji sebuah matan hadist maka sumber datanya adalah kitab hadist itu sendiri yaitu kitab arba’in nawawi yang dikarang oleh Abu Zakaria muhyiddin an-Nawawi dan syarah kitabnya serta beberapa buku terjemahnya. Data dalam penelitian ini berisikan analisis matan hadit yang berupa kata, frasa, dan kalimat yang berkaitan dengan makna tekstual dan kontekstual matan hadist bab niat. Teknik pengumpulan data dengan pembacaan, mengamatan dan penganalisisan melalui pendekatan semantik.